A novel predictor of unsustained return of spontaneous circulation in cardiac arrest patients through a combination of capnography and pulse oximetry: a multicenter observational study - Yang, Jing; Tang, Hanqi; Shao, Shihuan; Xu, Feng; Fu, Yangyang; Xu, Shengyong; Li, Chen; Li, Yan; Liu, Yang; Harold Walline, Joseph; Zhu, Huadong; Chen, Yuguo; et al. (World journal of emergency medicine, 2024)
Unsustained return of spontaneous circulation (ROSC) is a critical barrier to survival in cardiac arrest patients. This study examined whether end-tidal carbon dioxide (ETCO ) and pulse oximetry photoplethysmogram (POP) parameters can be used to identify unsustained ROSC. We conducted a multicenter observational prospective cohort study of consecutive patients with cardiac arrest from 2013 to 2014. Patients' general information, ETCO , and POP parameters were collected and statistically analyzed. The included 105 ROSC episodes (from 80 cardiac arrest patients) comprised 51 sustained ROSC episodes and 54 unsustained ROSC episodes. The 24-hour survival rate was significantly higher in the sustained ROSC group than in the unsustained ROSC group (29.2% vs. 9.4%, <0.05). The logistic regression analysis showed that the difference between after and before ROSC in ETCO (ΔETCO ) and the difference between after and before ROCS in area under the curve of POP (ΔAUCp) were independently associated with sustained ROSC (odds ratio [ ]=0.931, 95% confidence interval [95% ] 0.881-0.984, =0.011 and =0.998, 95% 0.997-0.999, <0.001). The area under the receiver operating characteristic curve of ΔETCO , ΔAUCp, and the combination of both to predict unsustained ROSC were 0.752 (95% 0.660-0.844), 0.883 (95% 0.818-0.948), and 0.902 (95% 0.842-0.962), respectively. Patients with unsustained ROSC have a poor prognosis. The combination of ΔETCO and ΔAUCp showed significant predictive value for unsustained ROSC.